Reduction of the residual warpage of fused deposition modeling by negative thermal expansion filler - Masaya Sakagami; Saito Ishiue; Maiki Kawaguchi; Akihiro Takezawa (Materials & Design)
We investigated the suppression of residual warpage using a negative thermal expansion (NTE) material filler, Zn1.6Mg0.4P2O7. To focus on the effect of thermal expansion on residual warpage, we used acrylonitrile-butadiene-styrene, which is an amorphous polymer with a small volume change around the liquid–solid phase transition, as the matrix. Composite pellets were prepared using a kneader, and filaments were produced for fused deposition modeling (FDM) using an extruder. We fabricated a bar-like test piece using a standard FDM machine and measured the warpage deformation using 3D scanning. The experimental results were supported by the finite element method. We also compared similarly sized SiO2 powders to discuss the advantages of NTE over conventional fillers. The warpage of a 100 mm x 5 mm x 2 mm bar-like test piece was reduced by approximately 75% by introducing Zn1.6Mg0.4P2O7 at 40 vol%. The effect of Zn1.6Mg0.4P2O7 at 30 vol% is similar to that of a conventional SiO2 filler at 40 vol%. Reducing the residual deformation through fillers would reduce energy consumption and simplify the device by avoiding build stage and chamber heating.